2005
DOI: 10.1111/j.1538-7836.2005.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial microparticles induce formation of platelet aggregates via a von Willebrand factor/ristocetin dependent pathway, rendering them resistant to dissociation

Abstract: Summary. Endothelial microparticles (EMP) released from activated or apoptotic endothelial cells (EC) are emerging as useful markers for detection of EC dysfunction. Our recent observation that EMP carry von Willebrand factor (vWf) led us to investigate their interaction with platelets. EMP were incubated with normal washed platelets in the presence or absence of ristocetin, then platelet aggregates were measured by flow cytometry. In the absence of ristocetin, negligible EMP conjugated with platelets (< 5%) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 42 publications
2
76
2
1
Order By: Relevance
“…20 We found that, within 1 hour, elevated circulating procoagulant, platelet, and EMPs are significantly reduced. Clearance rate differed by cellular origin so that erythrocyte-derived microparticles had not declined as much and 21 they present a potential thrombotic risk, which might explain their apparently more rapid clearance mechanism. However, EMP response to cardiac stress, in general, differed.…”
Section: Discussionmentioning
confidence: 99%
“…20 We found that, within 1 hour, elevated circulating procoagulant, platelet, and EMPs are significantly reduced. Clearance rate differed by cellular origin so that erythrocyte-derived microparticles had not declined as much and 21 they present a potential thrombotic risk, which might explain their apparently more rapid clearance mechanism. However, EMP response to cardiac stress, in general, differed.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, EMPs carry von Willebrand factor promoting platelet aggregation. 7 Levels of EMP-platelet aggregates have been found to be significantly higher in patients with stable coronary artery disease but diminished in acute phase of myocardial infarction, typical condition of platelet-dependent thrombosis. 8 EMPs and EMP-monocyte conjugates are elevated in patients with venous thromboembolism and are believed to play important role in thrombogenesis and reflect marked activation of endothelium, platelets and leukocytes which occurs in relation to thrombotic disorders.…”
Section: Endothelial Microparticles As a Mirror Of Endothelial Functionmentioning
confidence: 99%
“…They usually measure from 100 to 500 nm in diameter, and are released by budding from the surface membranes of activated platelets, after platelet attachment to endothelial-lined inner surfaces of the vessel wall, during normal hemostasis 62 (Table 2). First referred to as 'platelet dust,' circulating MVs are CD 42 positive (indicating their origin from platelets) and contain platelet-derived tissue factor (TF) and von Willebrand's factor (VWF), 30,63 which are the major initiators of intravascular coagulation in normal processes and in thromboembolic diseases. 30 Platelet release of extracellular MPs also increases during the tightly regulated process of platelet apoptosis, and is dependent on the formation of mitochondrial permeability transition pore.…”
Section: Diseases In Which Mvs Have a Role In Pathogenesis Atherosclementioning
confidence: 99%